Dietary n-3 Fatty Acids Inhibit Fever Induced by Inflammation in the Rat - A. L. Cooper; A. V. Turnbull; S. J. Hopkins; N. J. Rothwell (Hindawi Limited, 1994)
Modification of endogenous eicosanoid synthesis by dietary n-3 fatty acid supplementation reduces febrile responses, but the mechanisms underlying these effects in vivo have not been determined. In the present study, local inflammation was induced by intramuscular injection ofturpentine in rats fed control or n-3 supplemented diets for 8-9 weeks. In animals fed the control diet, turpentine induced fever, hypermetabolism, marked local inflammation (oedema), increased plasma IL-6 concentrations and raised cerebrospinal fluid (CSF) concentrations of PGE2. N-3 fatty acid supplementation significantly inhibited the rise in CSF PGE2, fever and hypermetaboHsm induced by turpentine. Local inflammation and increased plasma IL-6 concentrations were not affected by n-3 supplementation. These findings suggest that modification of dietary fat intake inhibits fever via reduced release of prostaglandins, probably within the brain, but does not affect the local or afferent signals involved in fever generation.